2002
DOI: 10.1046/j.1365-2400.2002.00252.x
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of air, sound and acoustic bubble screens in deflecting Atlantic salmon, Salmo salar L., smolts in the River Frome, UK

Abstract: Atlantic salmon, Salmo salar L., smolts are vulnerable to entrainment in a variety of man‐made structures as they migrate downstream. The ability of acoustic bubble screens to deflect smolts from potential hazards was assessed. Screens were deployed, in turn, across one of the two identical channels through which the millstream of the River Frome flowed and the efficiency of these screen systems was tested by counting smolts by video recording in each channel. It was concluded that these screens deflected a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 13 publications
3
66
1
Order By: Relevance
“…Recent studies have demonstrated behavioural avoidance in smolts related to hydraulic conditions (Haro et al 1998;Enders et al 2009), in-stream structures (Kemp and Williams 2008), overhead cover and absence of visual clues (Kemp et al 2005;Kemp and Williams 2009). Moreover, fish guidance may be accomplished using strobe lights (Johnson et al 2005), bubble curtains and sounds (Welton et al 2002;Sonny et al 2006) and deep, mid-channel furrows (Svendsen et al 2007). These findings indicate that smolts can be guided rapidly past the water withdrawal zone and over the weir crest to ensure passage.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have demonstrated behavioural avoidance in smolts related to hydraulic conditions (Haro et al 1998;Enders et al 2009), in-stream structures (Kemp and Williams 2008), overhead cover and absence of visual clues (Kemp et al 2005;Kemp and Williams 2009). Moreover, fish guidance may be accomplished using strobe lights (Johnson et al 2005), bubble curtains and sounds (Welton et al 2002;Sonny et al 2006) and deep, mid-channel furrows (Svendsen et al 2007). These findings indicate that smolts can be guided rapidly past the water withdrawal zone and over the weir crest to ensure passage.…”
Section: Resultsmentioning
confidence: 99%
“…The detailed operation of the counter has been described (Welton et al 2002), but essentially the smolts are diverted from the main River Frome with the aid of an acoustic bubble screen into the East Stoke millstream that flows through a fluvarium. Fish are then counted without handling as they pass through resistivity counting tubes.…”
Section: Methodsmentioning
confidence: 99%
“…Salmonids have been observed to avoid areas with continuous overhead cover (e.g. Welton et al 2002 for Atlantic salmon smolts) such as at culverts. In an experimental study, actively migrating Chinook salmon smolts encountered a divergence of downstream route through two channels (Kemp et al 2005).…”
Section: Physical Structure and Habitat Fragmentation: Culvert Restormentioning
confidence: 99%